Effects of Development of Supervision through GROW Coaching Model on Implementation of Nursing Process among Nurses at the Intensive Care Units in a Tertiary Hospital - Meejaidee, Kulchana; Sritoomma, Netchanok; Chatdokmaiprai, Kannikar (Journal of The Royal Thai Army Nurses, 2025)
This participatory action research aims to develop GROW coaching model and study the results of development of supervision through GROW coaching model on implementation of nursing process among nurses at the intensive care unit in a tertiary hospital. The research method is divided into three phases: 1) analyzing the situation, 2) developing a supervision model based on the growth coaching model, and 3) studying the results of developing supervision according to the growth coaching model. The target group is the quality development team, operational team of 28 people, and nursing records. The research instrument include 1) a semi-structured interview form, 2) a nursing record completeness assessment form, and 3) a questionnaire about the use of the nursing process. This study had a content validity of 1.0,1.0,0.98 respectively. The reliability of the questionnaire on the Implementation of the nursing process was 0.97. Data were analyzed by using percentage, mean, standard deviation, Wilcoxon matched-pairs signed-rank test. and content analysis. The results of Phase 1 from the interviews revealed that the traditional supervision was a one-time, non-continuous pre-work training. There was advisor to help and give advice. Phase 2 development of supervision according to the GROW coaching model, setting goals, current situation, selecting, and finalizing the preparation of a manual for using the nursing process. Phase 3 study of the results of the development of supervision according to the GROW coaching model, which found that the use of the nursing process in every aspect was complete and the use of the nursing process was higher after development than before receiving the supervision development program according to the GROW coaching model is statistically significant (p < .05). In this research identified that nursing administrators can lead the results of developing supervision according to the GROW coaching model and can be used to develop nurses to use the nursing process in intensive care units.